WORK POSITION AND LOW BACK PAIN IN ELDERLY FARMER - Abdul Muhith (UPT Penerbitan Universitas Jember, 2017)
Background: Low Back Pain is one of the disturbances that occur in the body due to the activities of the human body during the move with an unsafe position. The agricultural sector is one type of work that has a high risk for its workers. Extreme environmental conditions and traditional equipment determine the level of health and safety of farmers. The aim of this study was to determine the relationship between a work position and low back pain in the elderly farmer, Methods: This research was quantitative research with an analytic observational method, used crossectional design with Simple random sampling technique. The sample size was 45 farmers. This research was conducted in March 2017 in Sumengko village Mojokerto. Results: The result showed that most of the respondents are at the high-risk level (73,3%), meaning that the elderly farmers work in nonergonomic position. Low back pain experienced by most farmers is on the level of moderate complaints with 40 respondents (88.89%). Based on Spearman rank statistical test with a value of α = 0.05 significance level obtained result of 0.02, so there is a significant relationship between the working position of elderly farmers with the risk of low back pain in the Sumengko Mojokerto. Conclusions: Elderly farmers have low back pain complaints at moderate level, this is influenced by the unergonomic working position of farmers. So the farmers should keeping their body in good condition and also minimize the risk of getting low back pain. Keywords: work position, elderly farmers, low back pain